Pulses, Importance and Constraints - Pooja, Gottimukkula Sree; Naik, M. Ramesh; Teja, R. Ravi (Chronicle of Bioresource Management, 2021)
Pulses are a crucial component of global and Indian agriculture, contributing significantly to food security, nutrition, and sustainable farming practices. India is the largest producer of pulses, cultivating over 28 million hectares and contributing 31% of the world’s pulse production. Major pulses include gram (45% of total production), tur (17%), urd (11%), and mung (10%). As legumes, they enhance soil fertility by fixing 20–25 kg of atmospheric nitrogen per hectare, reducing dependence on synthetic fertilizers and promoting sustainable agriculture. Pulses are also a rich source of plant-based protein (20-25%), dietary fiber, essential amino acids, vitamins, and minerals such as iron and calcium, making them vital for balanced diet. Despite their importance, pulse production in India faces several constraints, including fluctuating climatic conditions, marginal land cultivation, lack of irrigation, and limited access to improved seed varieties. Socio-economic and agronomic challenges further hinder productivity. Addressing these constraints through improved agricultural practices, better post-harvest management, and policy interventions can enhance pulse production and ensure a more resilient and sustainable food system.